Lithium ion battery diaphragm and preparation method thereof
By adjusting the cutting position of antioxidants and using specific materials, the problems of decreased molecular residual amount and decomposition of antioxidants during processing of lithium-ion battery separators are solved, and the ability to retain and capture oxygen in the membrane molecular chain length is achieved. Improved, improves the performance of the diaphragm.
Patent Information
- Application Number
- CN202411343857.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-07
AI Technical Summary
During the processing of existing lithium-ion battery separators, polymer materials are easily decomposed, resulting in a decrease in molecular residual amount, antioxidants are heated and decomposed under high temperature environments, and their ability to capture oxygen decreases, affecting the performance of the separator.
By adjusting the feeding position of the antioxidant, it is fed in the fifth cylinder of the extruder, avoiding the large amount of heat energy generated by the screw shear force, and decomposing the antioxidant, using microporous polymers and pores The agent and hindered phenolic antioxidant are melt-kneaded and stretched to form a cast sheet and sliced to obtain a separator.
Without affecting the quality of the finished diaphragm, the molecular residual amount of the finished diaphragm is increased, more molecular chain length is retained, the oxygen capture ability of antioxidants is improved, and the performance of the diaphragm is enhanced.
Smart Images

Figure BDA0005060425820000071
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium ion battery separator and a preparation method thereof. Background Art
[0002] With the development of the times and the advancement of science and technology, the demand for energy is increasing day by day, and the oil and coal resources are approaching exhaustion, forcing people to seek new ways of energy supply and improve energy utilization. Secondary batteries came into being. In 1859, the first secondary battery, lead-acid battery, came out, followed by nickel-cadmium batteries, lithium batteries, and sodium rechargeable batteries. In the large-scale development of the modern new energy industry, lithium-ion batteries have been widely studied, industrialized and used on a large scale due to their high energy density, high output voltage, strong output power, high charging efficiency, low self-discharge loss, and wide operating temperature range. Lithium-ion batteries are composed of positive electrodes, diaphragms, electrolytes, negative electrodes, and shells. In lithium-ion batteries, the diaphragm can prevent direct contact between the positive and negative electrodes, and provide a channel for lithium ions to travel back and forth between the positive and negative electrodes, which plays an extremely important role in the normal and safe use of lithium-ion batteries.
[0003] At present, diaphragm materials are needed in lithium-ion batteries. The conventional raw materials on the market are high molecular polymers such as PE, PP, and PPS. However, high molecular materials are easily decomposed during the processing, resulting in a decrease in the molecular residue of the final finished film and a decrease in the tensile properties of the film material. Therefore, antioxidants are needed, but antioxidants will also partially decompose under high temperature conditions. Summary of the invention
[0004] Based on this, the purpose of the present invention is to provide a lithium-ion battery separator and a preparation method thereof. The preparation method reduces the degree of decomposition of the antioxidant during the processing by adjusting the feeding position of the antioxidant, thereby increasing the molecular residue of the finished separator without affecting the quality of the finished separator, thereby retaining more molecular chain length.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a method for preparing a lithium ion battery separator, which comprises the following steps: mixing a microporous polymer and a pore-forming agent and feeding them into the first section of a barrel of an extruder, feeding an antioxidant into a side feeding port of the extruder, and the fifth section of the barrel of the side feeding port, melt-kneading, and casting through a die to form a cast sheet, and then through longitudinal drawing, transverse drawing, and traction devices to extract the pore-forming agent in the separator, and then cutting to obtain the separator.
[0007] The present invention adjusts the feeding position of the antioxidant to avoid the large amount of heat energy generated by the shear force of the screw in the first four sections of the barrel causing the antioxidant to decompose, resulting in a decrease in the antioxidant's ability to capture oxygen. Under the premise of not affecting the quality of the finished diaphragm, the residual amount of molecules in the finished diaphragm is increased, and more molecular chain length can be retained.
[0008] As a further improvement of the above solution of the present invention, the microporous polymer is polyphenylene sulfide, polyethylene, or polypropylene.
[0009] As a further improvement of the above solution of the present invention, the microporous polymer is polyethylene with a molecular weight of 60W.
[0010] As a further improvement of the above solution of the present invention, the antioxidant is a hindered phenol antioxidant.
[0011] As a further improvement of the above solution of the present invention, by weight percentage, the added amount of the microporous polymer is 20%-25%, the added amount of the pore former is 75%-80%, and the added amount of the antioxidant is 0.1-0.5%.
[0012] As a further improvement of the above solution of the present invention, by weight percentage, the added amount of the microporous polymer is 22%, the added amount of the pore former is 77.7%, and the added amount of the antioxidant is 0.3%.
[0013] As a further improvement of the above solution of the present invention, the hindered phenol antioxidant is Irganox1098 or Irganox1010.
[0014] As a further improvement of the above solution of the present invention, the pore-forming agent is paraffin oil.
[0015] The present invention provides a lithium ion battery separator, which is prepared by the above-mentioned method for preparing the lithium ion battery separator.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] 1. The present invention adjusts the feeding position of the antioxidant to avoid the large amount of heat energy generated by the shear force of the screw in the first four sections of the barrel causing the antioxidant to decompose, resulting in a decrease in the antioxidant's ability to capture oxygen. Under the premise of not affecting the quality of the finished diaphragm, the residual amount of molecules in the finished diaphragm is increased, and more molecular chain length can be retained. DETAILED DESCRIPTION
[0018] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0019] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0020] Example 1
[0021] This embodiment provides a lithium ion battery separator, and the preparation method thereof comprises the following steps:
[0022] 466.2 kg of paraffin oil was measured and preheated in a water bath at 80°C for 30 min, and then 132 kg of polyethylene PE (60W molecular weight) powder was added, and stirred with a stirrer for 3 h until the PE powder was evenly dispersed in the paraffin oil to obtain a mixture of paraffin oil and PE powder; 1 kg of hindered phenol antioxidant Irganox1098 was weighed into a loss-in-weight weighing scale, and the feed rate was set to 0.6 kg / h;
[0023] A twin-screw extruder with a length-to-diameter ratio of 64:1 was used. After the extruder temperature was raised to 200°C and kept warm for 3 hours, a mixture of paraffin oil and PE powder was slowly added to the first barrel of the twin-screw extruder, and the extruder speed was gradually increased to 400 rpm. The loss-in-weight scale was then turned on to feed the hindered phenol antioxidant Irganox 1098 into the fifth barrel of the twin-screw extruder. The melt was cast through the extruder die, cooled and crystallized in a cooling water tank to form a casting sheet, and then passed through longitudinal drawing, transverse drawing, and traction devices to extract the pore-forming agent in the diaphragm, and then the diaphragm was obtained by slitting.
[0024] Example 2
[0025] This embodiment provides a lithium ion battery separator, and the preparation method thereof comprises the following steps:
[0026] 466.2 kg of paraffin oil was measured and preheated in a water bath at 80°C for 30 min, and then 132 kg of polyethylene PE (60W molecular weight) powder was added, and stirred with a stirrer for 3 h until the PE powder was evenly dispersed in the paraffin oil to obtain a mixture of paraffin oil and PE powder; 1 kg of hindered phenol antioxidant Irganox1098 was weighed into a loss-in-weight weighing scale, and the feed rate was set to 1.8 kg / h;
[0027] A twin-screw extruder with a length-to-diameter ratio of 64:1 was used. After the extruder temperature was raised to 200°C and kept warm for 3 hours, a mixture of paraffin oil and PE powder was slowly added to the first barrel of the twin-screw extruder, and the extruder speed was gradually increased to 400 rpm. The loss-in-weight scale was then turned on to feed the hindered phenol antioxidant Irganox 1098 into the fifth barrel of the twin-screw extruder. The melt was cast through the extruder die, cooled and crystallized in a cooling water tank to form a casting sheet, and then passed through longitudinal drawing, transverse drawing, and traction devices to extract the pore-forming agent in the diaphragm, and then the diaphragm was obtained by slitting.
[0028] Example 3
[0029] This embodiment provides a lithium ion battery separator, and the preparation method thereof comprises the following steps:
[0030] 466.2 kg of paraffin oil was measured and preheated in a water bath at 80°C for 30 min, and then 132 kg of polyethylene PE (60W molecular weight) powder was added, and stirred with a stirrer for 3 h until the PE powder was evenly dispersed in the paraffin oil to obtain a mixture of paraffin oil and PE powder; 1 kg of hindered phenol antioxidant Irganox1098 was weighed into a loss-in-weight weighing scale, and the feed rate was set to 3 kg / h;
[0031] A twin-screw extruder with a length-to-diameter ratio of 64:1 was used. After the extruder temperature was raised to 200°C and kept warm for 3 hours, a mixture of paraffin oil and PE powder was slowly added to the first barrel of the twin-screw extruder, and the extruder speed was gradually increased to 400 rpm. The loss-in-weight scale was then turned on to feed the hindered phenol antioxidant Irganox 1098 into the fifth barrel of the twin-screw extruder. The melt was cast through the extruder die, cooled and crystallized in a cooling water tank to form a casting sheet, and then passed through longitudinal drawing, transverse drawing, and traction devices to extract the pore-forming agent in the diaphragm, and then the diaphragm was obtained by slitting.
[0032] Comparative Example 1
[0033] This comparative example proposes a lithium ion battery separator, and its preparation method comprises the following steps:
[0034] 466.2 kg of paraffin oil was measured and preheated in a water bath at 80° C. for 30 min, and then 132 kg of polyethylene PE (60W molecular weight) powder and 0.6 kg of hindered phenolic antioxidant Irganox 1098 were weighed and stirred for 3 h using a stirrer until the PE powder and the hindered phenolic antioxidant Irganox 1098 were evenly dispersed in the paraffin oil to obtain a mixture of paraffin oil, PE powder and hindered phenolic antioxidant Irganox 1098;
[0035] A twin-screw extruder with a length-to-diameter ratio of 64:1 was used. After the extruder temperature was raised to 200°C and kept warm for 3 hours, a mixture of paraffin oil, PE powder, and hindered phenol antioxidant Irganox1098 was slowly added to the first barrel of the twin-screw extruder, and the extruder speed was gradually increased to 400 rpm. The melt was cast through the extruder die, cooled and crystallized in a cooling water tank to form a casting sheet, and then passed through longitudinal drawing, transverse drawing, and traction devices to extract the pore-forming agent in the diaphragm, and then the diaphragm was obtained by slitting.
[0036] Comparative Example 2
[0037] This comparative example proposes a lithium ion battery separator, and its preparation method comprises the following steps:
[0038] 466.2 kg of paraffin oil was measured and preheated in a water bath at 80° C. for 30 min, and then 132 kg of polyethylene PE (60W molecular weight) powder and 1.8 kg of hindered phenol antioxidant Irganox 1098 were weighed and stirred for 3 h using a stirrer until the PE powder and the hindered phenol antioxidant Irganox 1098 were evenly dispersed in the paraffin oil to obtain a mixture of paraffin oil, PE powder and hindered phenol antioxidant Irganox 1098;
[0039] A twin-screw extruder with a length-to-diameter ratio of 64:1 was used. After the extruder temperature was raised to 200°C and kept warm for 3 hours, a mixture of paraffin oil, PE powder, and hindered phenol antioxidant Irganox1098 was slowly added to the first barrel of the twin-screw extruder, and the extruder speed was gradually increased to 400 rpm. The melt was cast through the extruder die, cooled and crystallized in a cooling water tank to form a casting sheet, and then passed through longitudinal drawing, transverse drawing, and traction devices to extract the pore-forming agent in the diaphragm, and then the diaphragm was obtained by slitting.
[0040] Comparative Example 3
[0041] This comparative example proposes a lithium ion battery separator, and its preparation method comprises the following steps:
[0042] 466.2 kg of paraffin oil was measured and preheated in a water bath at 80° C. for 30 min, and then 132 kg of polyethylene PE (60W molecular weight) powder and 3 kg of hindered phenolic antioxidant Irganox 1098 were weighed and stirred for 3 h using a stirrer until the PE powder and the hindered phenolic antioxidant Irganox 1098 were evenly dispersed in the paraffin oil to obtain a mixture of paraffin oil, PE powder and hindered phenolic antioxidant Irganox 1098;
[0043] A twin-screw extruder with a length-to-diameter ratio of 64:1 was used. After the extruder temperature was raised to 200°C and kept warm for 3 hours, a mixture of paraffin oil, PE powder, and hindered phenol antioxidant Irganox1098 was slowly added to the first barrel of the twin-screw extruder, and the extruder speed was gradually increased to 400 rpm. The melt was cast through the extruder die, cooled and crystallized in a cooling water tank to form a casting sheet, and then passed through longitudinal drawing, transverse drawing, and traction devices to extract the pore-forming agent in the diaphragm, and then the diaphragm was obtained by slitting.
[0044] Comparative Example 4
[0045] This comparative example proposes a lithium ion battery separator, and its preparation method comprises the following steps:
[0046] 466.2 kg of paraffin oil was measured and preheated in a water bath at 80°C for 30 min, and then 132 kg of polyethylene PE (60W molecular weight) powder was added, and stirred with a stirrer for 3 h until the PE powder was evenly dispersed in the paraffin oil to obtain a mixture of paraffin oil and PE powder; 1 kg of hindered phenol antioxidant Irganox1098 was weighed into a loss-in-weight weighing scale, and the feed rate was set to 1.8 kg / h;
[0047] A twin-screw extruder with a length-to-diameter ratio of 64:1 was used. After the extruder temperature was raised to 200°C and kept warm for 3 hours, a mixture of paraffin oil and PE powder was slowly added to the first barrel of the twin-screw extruder, and the extruder speed was gradually increased to 400 rpm. The loss-in-weight scale was then turned on to feed the hindered phenol antioxidant Irganox 1098 into the fourth barrel of the twin-screw extruder. The melt was cast through the extruder die, cooled and crystallized in a cooling water tank to form a casting sheet, and then passed through longitudinal drawing, transverse drawing, and traction devices to extract the pore-forming agent in the diaphragm, and then the diaphragm was obtained by slitting.
[0048] Comparative Example 5
[0049] This comparative example proposes a lithium ion battery separator, and its preparation method comprises the following steps:
[0050] 466.2 kg of paraffin oil was measured and preheated in a water bath at 80°C for 30 min, and then 132 kg of polyethylene PE (60W molecular weight) powder was added, and stirred with a stirrer for 3 h until the PE powder was evenly dispersed in the paraffin oil to obtain a mixture of paraffin oil and PE powder; 1 kg of hindered phenol antioxidant Irganox1098 was weighed into a loss-in-weight weighing scale, and the feed rate was set to 1.8 kg / h;
[0051] Using a twin-screw extruder with a length-to-diameter ratio of 64:1, after the extruder temperature was raised to 200°C and kept warm for 3 hours, the mixture of paraffin oil and PE powder was slowly added to the first barrel of the twin-screw extruder, and the extruder speed was gradually increased to 400 rpm. Then, the loss-in-weight scale was turned on and the hindered phenol antioxidant Irganox 1098 was fed into the sixth barrel of the twin-screw extruder. The melt cast from the extruder die had low transparency and could not be stretched into a film normally.
[0052] Test Case
[0053] The cast pieces of Examples 1-3 and Comparative Examples 1-5 were cut and tested for melt index and molecular weight. The melt index test standard was GB / T3682, and the molecular weight test standard was CB / T1632-93. The test results are shown in Table 1.
[0054] Table 1 Performance test results
[0055]
[0056]
[0057] From the results in Table 1, we can see that:
[0058] By comparing Example 1 with Comparative Example 1, it can be seen that when the antioxidant content is the same as 0.1%, the antioxidant of Example 1 is fed from the 5th barrel, and the molecular residue of Example 1 is 460,000, which is higher than the molecular residue of 418,000 of the antioxidant fed from the first barrel in Comparative Example 1, which is about 10% higher.
[0059] By comparing Example 2 with Comparative Example 2, it can be seen that when the antioxidant content is the same as 0.3%, the antioxidant of Example 2 is fed from the 5th section, and the molecular residue of Example 2 is 488,000, which is higher than the molecular residue of 430,900 of the antioxidant fed from the first section of the cylinder in Comparative Example 2, which is about 13.2% higher.
[0060] By comparing Example 3 with Comparative Example 3, it can be seen that when the antioxidant content is the same as 0.5%, the antioxidant of Example 3 is fed from the fifth section, and the molecular residue of Example 3 is 510,000, which is higher than the molecular residue of 442,000 of the antioxidant fed from the first section of the cylinder in Comparative Example 3, which is about 15.4% higher.
[0061] By comparing Example 2 with Comparative Example 4, it can be seen that when the antioxidant content is the same as 0.3%, the antioxidant of Example 2 is fed from the fifth section, and the molecular residue of Example 2 is 488,000, which is higher than the molecular residue of 465,000 in Comparative Example 4 when the antioxidant is fed from the fourth section of the cylinder, which is about 4.9% higher.
[0062] In Comparative Example 5, the antioxidant was fed too far back, resulting in poor dispersion and failure to stretch the finished film.
[0063] In summary, when the antioxidant is fed from the 5th section of the cylinder, the molecular residual amount will be higher than the molecular residual amount when it is fed from the 1st section, and the antioxidant's ability to capture oxygen is stronger when it is fed from the 5th section of the cylinder.
[0064] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0065] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a lithium ion battery separator, characterized in that: It includes the following steps: The microporous polymer and the pore-forming agent are mixed and put into the first barrel of the extruder, and the antioxidant is put into the fifth barrel of the extruder, melt-kneaded, and cast through a die. After passing through longitudinal drawing, transverse drawing and traction devices, the pore-forming agent in the diaphragm is extracted, and then the diaphragm is obtained by cutting.
2. The method for preparing a lithium ion battery separator according to claim 1, characterized in that: The microporous polymer is polyphenylene sulfide 、 Polyethylene, Polypropylene.
3. The method for preparing a lithium ion battery separator according to claim 1, characterized in that: The microporous polymer is polyethylene PE with a molecular weight of 60W.
4. The method for preparing a lithium ion battery separator according to claim 1, characterized in that: The antioxidant is a hindered phenol antioxidant.
5. The method for preparing a lithium ion battery separator according to claim 1, characterized in that: By weight percentage, the addition amount of the microporous polymer is 20%-25%, the addition amount of the pore-forming agent is 75%-80%, and the addition amount of the antioxidant is 0.1-0.5%.
6. The method for preparing a lithium ion battery separator according to claim 5, characterized in that: By weight percentage, the added amount of the microporous polymer is 22%, the added amount of the pore former is 77.7%, and the added amount of the antioxidant is 0.3%.
7. The method for preparing a lithium ion battery separator according to claim 3, characterized in that: The hindered phenol antioxidant is Irganox1098 or Irganox1010.
8. The method for preparing a lithium ion battery separator according to claim 1, characterized in that: The pore-forming agent is paraffin oil.
9. A lithium ion battery separator, characterized in that: The lithium ion battery separator is prepared by the method for preparing the lithium ion battery separator according to any one of claims 1 to 8.